Composite radial filter for removal of agrochemicals from agricultural runoff. Issue 6 (11th June 2022) - Hansra, G. D. S.; Singh, J. P.; Sahota, P. P.
Abstract: A composite radial filter was designed, fabricated and developed for the removal of agrochemicals particularly N, P, K and bacteriological contaminant in runoff water from rice field for recharging aquifer. Zeolite (Z), activated charcoal (C), coarse sand (CS) and gravel (G) filter materials were placed in annular concentric rings of composite radial filter in different combination of thickness in the ratio of 1:2:4:4, 1:3:4:4, 1:2:2:4, 1:3:2:4 and 0:2:1:2 for five treatments (T1, T2, T3, T4 and T5 ) respectively. Sodium hypochlorite solution (5%) injected at the rate of 0.1 ml per unit discharge (lps) through chlorination unit at the outlet of the radial filter decreased bacteriological contamination to <10 MPN per 100 ml from 1, 100 MPN per 100 ml of filtered water. The performance of composite radial filter was evaluated by analyzing filtered water samples for four inflow/outflow rates viz . 0.42, 0.82, 1.24 and 1.66 lps. The T5 treatment consisting of filter materials C, CS and G with thickness of 20, 10 and 20 cm respectively was found to be the best compared to the other four treatments. The filter materials were washed with fresh water after 5 hours of filtration and reused. HIGHLIGHTS: A composite radial filter was developed for the removal of agrochemicals from rice fieldrunoff water for recharging aquifer. Activated charcoal (C), coarse sand (CS) and gravel (G) filter materials in compositeradial filter with thickness ratio of 2:2 (20, 10 and 20 cm) respectively were found to be the best. The filter materials after 5 hours of operation could be reused after washing with fresh water.